Poradnictwo zawodowe dla żydowskiej młodzieży szkolnej w Polsce w okresie międzywojennym - Łapot, Mirosław (Biuletyn Historii Wychowania, 2020)
This article presents the beginnings of vocational counselling for school-attending adolescents in Poland. Vocational counselling developed in Poland in the Interwar period as a sub-discipline of applied psychology. The Jewish minority largely contributed to the development of this movement with Lvov at centre of it. Jews established a vocational counselling and psycho-technical institutes, putting the emphasis on school-attending adolescents and apprentices in craft companies, as well as developing new tools for psycho-technical measurements. Zionism was one of the reasons for the development of Jewish vocational counselling for young people. Zionists believed that young Jews should acquire a profession that would allow Jewish settlement in Palestine. This article also presents Zofia Lipszyc, Adolf Berman, Lea Fejgin-Gartensteyg, Jakub Kessler and Józef Weinbaum, unknown Jewish psychologists and psychotechcians.